Awake Aneurysm Clipping: Challenges Conquered - Kaur, Kirandeep; Thappa, Priya; Luthra, Ankur; Chauhan, Rajeev; Panda, Nidhi; Sahoo, Sushanta K. (Journal of Neuroanaesthesiology and Critical Care, 2023)
Microsurgical aneurysm clipping under general anesthesia is considered a definitive procedure for the obliteration of unruptured and ruptured aneurysms. Aneurysm clipping can present with postoperative neurological complications, which can be missed under general anesthesia even with intraoperative neurophysiological monitoring. Real-time monitoring with awake patients can help prevent and treat these complications very early. The anesthesiologist has a vital role in awake aneurysm surgery from providing adequate surgical conditions to patient satisfaction and managing intraoperative complications. We report the first-hand experience as a neuroanesthesiology team managing awake craniotomy and aneurysm clipping.
Keywords: awake craniotomy; dexmedetomidine; unruptured and aneurysm clipping